Cough 7: Current and future drugs for the treatment of chronic cough. Issue 5 (28th April 2004) - Belvisi, M G; Geppetti, P
Abstract : There are currently no effective treatments for controlling the cough response with an acceptable therapeutic ratio. However, several new mechanisms have been identified which may lead to the development of new drugs.